Gender and identity in contemporary Coptic society - Haddon, Hazel (AUC Knowledge Fountain, 2012)
This thesis attempts to analyze the role that class plays in determining attitudes to gender among upper middle class Egyptian Copts. Through fieldwork, it explores the relationship between class, religion and gender in the lives of upper middle class Christian women. It argues that members of the upper middle class share a common â class cultureâ and have access to â cosmpolitan capitalâ which is constituted largely in social, cultural, educational and linguistic terms, and which sets them apart from the broader middle class. A distinctive class culture is produced through gender ideologies (described using terms such as â open mindedâ and â educatedâ ) that distinguish the upper middle class from other socio-economic groups which enforce different gender norms. This class culture and the resources provided by cosmopolitan capital allow upper middle class Coptic women to selectively reinterpret some elements of mainstream Coptic Orthodox teaching on gender issues, particularly teachings that are not compatible with the kind of gender norms practiced within the upper middle class (for example, mixed gender friendships, and romantic relationships prior to engagement). These selective reinterpretations of gender norms are not rigorously policed by clerical authorities; but other areas of contestation between lay elites and church authorities do provoke reactions, particularly the struggles over divorce rights. Upper middle class Coptic women use gendered symbols (womenâ s dress, gender segregation etc.) to define the boundaries of their class and locate others in a particular class framework, showing that ideas about gender remain central to contesting and defining group identities.